Islam on the Move The Tablighi Jama'at in Southeast Asia - Noor, Farish A. (Amsterdam University Press, 2012)
Much nuance and variability have been lost in the process of the reductivist analysis of Islam post 9/11 and, as this study amply demonstrates, we are all the poorer as a result. This exhaustive examination of the rise and spread of the Tablighi Jama't, arguably the world's largest Islamic missionary movement, locates it in the larger perspective of global Islam and developments in the Muslim societies. Combining an overview of the history and current socio-political perception of the Tablighi Jama'at with a more analytical and philosophical approach to fundamental questions of identity, subject-positioning and representation, the author creates a comprehensive resource of interest to all scholars and students of Islam. Drawing on exhaustive research and records of conversion narratives of the new members of Tablighi Jama'at, cited here at length, the author creates a unique perspective on this complex phenomenon from both an internal and external viewpoints. Ahmad-Noor locates the spiritual framework of the movement in the context of its perception in the eyes of the political and religious authorities of the countries where it has a following, as well as the Western 'securocrat' approach.